Unlocking Innovation Potential: A Systematic Review of HRM Strategies for Fostering Creativity and Innovation in the Workplace - Polim, Adrian (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This systematic review explores the intricate dynamics of creativity and innovation within organizational contexts, with a specific focus on the role of Human Resource Management (HRM) strategies. The study begins by delineating the foundational definitions of creativity and innovation, emphasizing their symbiotic relationship as fundamental drivers of organizational change. Through an extensive review of literature, the pivotal importance of HRM strategies in fostering creativity and innovation emerges, with leadership within HRM identified as a key determinant of organizational culture conducive to innovation. The analysis highlights the bidirectional relationship between HRM practices and innovation outcomes, underscoring the transformative potential of strategic recruitment, training, performance management, and rewards and recognition. While recognizing inherent limitations, including biases in existing literature and contextual constraints, the study offers insights into future research directions, advocating for longitudinal studies, interdisciplinary approaches, and qualitative methodologies to deepen understanding of organizational creativity and innovation. In conclusion, this study serves as a stepping stone towards nurturing vibrant ecosystems of creativity and innovation within organizations, enriching lives and driving sustainable change.